A BRIEF INTRODUCTION TO SYMPLECTIC AND CONTACT MANIFOLDS - BANYAGA, Augustin; HOUENOU, Djidémè Franck (Nankai Tracts in Mathematics, 2016)
The book introduces the basic notions in Symplectic and Contact Geometry at the level of the second year graduate student. It also contains many exercises, some of which are solved only in the last chapter. We begin with the linear theory, then give the de nition of symplectic manifolds and some basic examples, review advanced calculus, discuss Hamiltonian systems, tour rapidly group and the basics of contact geometry, and solve problems in chapter 8. The material just described can be used as a one semester course on Symplectic and Contact Geometry. The book contains also more advanced material, suitable to advanced graduate students and researchers.